Response to Sea Ice Melt Indicates High Seeding Potential of the Ice Diatom Thalassiosira to Spring Phytoplankton Blooms: A Laboratory Study on an Ice Algal Community From the Sea of Okhotsk - Yan, Dong; Yoshida, Kazuhiro; Nishioka, Jun; Ito, Masato; Toyota, Takenobu; Suzuki, Koji (Frontiers in Marine Science, 2020)
Phytoplankton communities in seasonally ice-covered areas are largely affected by ice algae. The Okhotsk Sea is the southernmost sea ice zone in the northern hemisphere with a sizeable seasonal ice cover, thus ice algae of the Okhotsk sea ice have a large potential to seed the early spring bloom. Little is known about the Okhotsk ice algal communities and their seeding effects. We investigated the dynamics of the composition and the photophysiological performances of an Okhotsk ice algal community in a 6-day laboratory incubation experiment that simulated the natural ice melt conditions. Centric diatoms, especially Thalassiosira spp., overwhelmingly dominated the ice algal community throughout incubation, whereas pennate diatoms, mostly Navicula and Nitzschia, showed little growth with much higher mortality. The maximum photochemical efficiency of Photosystem II (Fv/Fm) was the lowest at the beginning of the ice melt, suggesting a suppressed photosynthetic functioning by changes in salinity. The cellular pigment contents decreased by 30% due to physical damage of the cellular membrane, evidenced by deformed plastids under a microscope. The transcript level of the rbcL gene that encodes the large subunit of RubisCO was significantly higher during ice melt and decreased in the no-ice period, suggesting an urgent need for osmoprotectants under the melt condition. Full recovery of photosynthesis and growth was also made after complete ice melt. Our results indicated high seeding potential of Thalassiosira to spring blooms owing to their photophysiological plasticity to dynamic salinity changes.